Analysis of a Detention Basin as a Flood Control Measure In Kedawung Village, Tanjung Subdistrict, Brebes Regency - Nanda Salsabila; Nurdiyanto Nurdiyanto (Journal of Social Research, 2026)
Flooding is a common problem in local communities due to heavy rainfall and limited drainage capacity. A detention basin is a flood control infrastructure designed to temporarily store surface runoff before releasing it downstream. This study analyzes the performance of a detention basin as a flood control measure using a flood routing approach, with emphasis on sluice gate opening variation and its effect on outflow behavior. The research employs quantitative hydrological and hydraulic analysis under three operational conditions: fully closed, half-open, and fully open sluice gate. Hydrological analysis includes the determination of design rainfall using a selected probability distribution with goodness of fit testing, followed by calculations of time of concentration, rainfall intensity, and design flood discharge. The resulting discharge is used as inflow in the flood routing simulation. Hydraulic analysis covers outflow computation through the sluice gate and evaluation of storage changes and water surface elevation within the basin. The relationship between inflow and outflow is examined to understand system response under different gate openings over time. The results show that for a 25-year return period, the design flood discharge is 4,060 m³/s with a time of concentration of 44.861 minutes. The flood discharge reduction under half-open sluice gate conditions reaches 64.4%, indicating a significant influence of gate operation on outflow regulation. In conclusion, detention basins play an important role in flood control through peak attenuation and flow delay, while sluice gate opening variation strongly affects flood routing performance and outflow characteristics